OBSTRUENT VOICING IN ENGLISH AND POLISH. A PEDAGOGICAL PERSPECTIVE - Gonet, Wiktor (International Journal of English Studies, 2001)
'Voicing' in English voiced obstruents has been defined in terms of 'full' vs. 'partial'. When teaching English pronunciation to native speakers of Polish, where voiced sounds can be only fully voiced, it is diffcult to make the students aware of the phonation strategy to be used to obtain 'partially voiced' sounds, especially in plosives. The accessability of digital speech analysis computer software has made it possible to visualize the acoustic properties of speech sounds which can facilitate the teaching of English pronunciation to Poles, providing a visual feedback in class and at home. This is necessary for obtaining the correct phonation control that functions with utmost precision measured in centiseconds. Yet speech visualisation for the purpose of teaching English phonetics in Poland is employed only at the author's institution, and the remaining hundreds of schools and universities do not take advantage of the possibilities modem technology offers. The 'pedagogical perspective' of the paper aims at exerting an encouraging impact both on teachers of phonetics and on students of English. The article also provides a description of Polish voicing rules and a detailed comparison of voicing in English and Polish obstruents based on the concept of Voice Onset Time.